2015
DOI: 10.1111/jac.12142
|View full text |Cite
|
Sign up to set email alerts
|

Lint Yield Compensatory Response to Main Stem Node Removal in Upland Cotton (Gossypium hirsutum)

Abstract: Hail storm damage to the cotton (Gossypium hirsutum L.) plants can destroy vegetative and reproductive structures, modify canopy architecture and impact lint yield. Field studies were conducted at University of Arizona Maricopa Agricultural Center in 2011, 2012 and 2013 to examine cotton plant architecture changes and compensatory growth in response to removal treatments of uppermost nodes on main stem (terminal bud removal, 2 node removal and 4 node removal) as simulation of hail damage at the node 2, 4, 8, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, Smith and Varvil (1981) also observed that when the same severity of damage occurred in older plants, decreased recoverability also occurred which contradicts the findings of this research. Additionally, research conducted by Yang, Kaggwa, Andrade‐Sanchez, Zarnstorff, and Wang (2016) found that yield loss due to main stem node removal was compensated by increased boll number on vegetative branches, thus resulting in no difference in yield response to main stem node removal. Results from this research indicate no yield penalty may be observed if mainstem node removal is low late in the season, but that yield penalties will be likely as even slight damage (two node removal) occurs early in the season (four‐leaf stage).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Smith and Varvil (1981) also observed that when the same severity of damage occurred in older plants, decreased recoverability also occurred which contradicts the findings of this research. Additionally, research conducted by Yang, Kaggwa, Andrade‐Sanchez, Zarnstorff, and Wang (2016) found that yield loss due to main stem node removal was compensated by increased boll number on vegetative branches, thus resulting in no difference in yield response to main stem node removal. Results from this research indicate no yield penalty may be observed if mainstem node removal is low late in the season, but that yield penalties will be likely as even slight damage (two node removal) occurs early in the season (four‐leaf stage).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the yield reduction at different damage stages was the premise of developing yield prediction model at different damage stages. This may be correlated with cotton recoverability following hail damage, which has been proven to decrease with increasing damage levels and damage to older plants (Longer & Oosterhuis, 1999; Smith & Varvil, 1981; Yang et al., 2016). At the early growth stage of cotton, defoliation changes the canopy structure of the plant, increases light interception of bottom leaves and the carbon dioxide absorption rate of remaining leaves, promoting the rapid increase of net photosynthetic rate and transportation of photosynthetic products to vegetative organs (Lu et al., 2019; Prins & Verkaar, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, hand‐harvesting in the United States has become a research tool, providing researchers and agronomists with a view into the subtle interactions between cotton plants in time and space. Each fruit on the plant represents an individual flowering date, so the distribution of fruit on the plant represents the plant's response to its environment (Hawkins & Peacock, 1973), including weather and water availability (Bauer, Foulk, Gamble, & Sadler, 2009; Bednarz & Nichols, 2005; Bednarz, Nichols, & Brown, 2006; Jenkins, McCarty, & Parrott, 1990; Snowden, Ritchie, Cave, Keeling, & Rajan, 2013), fertility (Bondada, Oosterhuis, Norman, & Baker, 1996; Boquet, Moser, & Breitenbeck, 1993), planting density (Bednarz et al., 2006; Sadras, 1997), weed and insect pressure (Bednarz & Roberts, 2001; Mills, Bednarz, Ritchie, & Whitaker, 2008; Sadras, 1995; Wilson, Sadras, Heimoana, & Gibb, 2003), and short‐term catastrophic events, such as hailstorms or off‐target chemical sprays (Byrd et al., 2016; Yang, Kaggwa, Andrade‐Sanchez, Zarnstorff, & Wang, 2016), all with respect to time.…”
Section: Introductionmentioning
confidence: 99%